Evaluation of deadspace effects created by heat and moisture exchange filter during artificial lung ventilation in newborns - A. N. Shmakov; K. V. Budarova; N. L. Elizar’eva; V. N. Kokhno (Сибирский научный медицинский журнал, 2022)
Heat and moisture exchange filters create additional dead space, comparable in volume to physiological, in premature newborns. It makes carbon dioxide remove difficultу. Reducing the dead space volume by increasing the flow in the ventilator circuit can lead to the hypocapnia. Aim of the study was to determine the safety and efficiency of gas flow boost in the ventilator circuit to hypercapnia compensation created by the additional dead space. Material and methods. The effect of the additional dead space created by a heat and moisture exchange filter on hemoglobin saturation and partial pressure of carbon dioxide at the end of expiration in premature newborns at flows of 5 and 6 l/min was studied. Results and discussion. It has been demonstrated that flows of 5–6 l/min satisfactorily compensate for the effect of additional deadspace without hypocapnia. Conclusions. It is possible to recommend the widespread use of heat and moisture exchange filters in newborn weighing at least 1.0 kg during long-term transportation.